CHANGING INSIGHT OF WELFARE AND UNIONISM (Third Sector Social Economic Review, 2014)
Power loss of unions which had occured as a result of the capitalist relations of production, and intend defending the rights of the workers based upon their social classes is witnessed since 1970's. This loss of power which is generally tried to be explained by the changes rised in industrial relations system, requires a more inclusive analysis covering also the change in welfare insight indeed. Welfare policies structured by full employment targeted Keynesian economy policies which are based upon the Fordist mass production can not respond to the new structure of society formalized by global markets. Traditional welfare understanding of wage earner society which solves social issues by solidarity dynamics in terms of social security, go towards a new way of searching as a result of changes occured in “working” concept. This change persists in the axis of flexibility, precarity, irregularity and “end of work” debates, altered the extent and the size of welfare services. The new welfare concept of ""lost"" or ""meaning lost"" working life based rights, especially the union rights, promises a more limited and temporal kind of rights. Built their existence on the dynamics of working life, unions' place and activity in the new welfare concept was often being subjected in academic study. This study aims to analyze unions' power loss, by presenting a perspective of changing appearance of welfare as well as the transformation of industrial relations system.
Keywords: Unionism; Welfare; Welfare State; Industrial Relations System